Decision factor towards product to become customer of bank BNI Batam branch in Indonesia - Dede Ansyari, Guci; Puspa Liza, Ghazali; Abdul Malek, A Tambi; Salman, Lambak; Hazimi, Mohd Foziah; Abdul Talib, Bon (2020)
This research focus on decision factor towards product to become customer of Bank BNI Batam Branch in Indonesia. The purpose of the research is to examine if there is any relationship between sales promotion and publicity as decision factor to become customer of Bank BNI Batam Branch in Indonesia. The data self-collected, using quantitative based-study. Data will be collect by surveyed questionnaire and be analyzed by using Statistical Package for the Social Science (SPSS). A hundred respondents of people who have become a customer on Bank BNI Batam Branch have been chosen in the field of research in Batam, Indonesia. The methode instrument was using questionnaires and made up of five variables. The questionnaires distributed were made up of three variables, where two were independent variables and one was dependent variable. By using multiple regression analysis, it is found that each independent variable has strong correlation with the single variable. it can be concluded that the sales promotion, publicity and become customer of Bank BNI Batam branch have a positive relationship.